Optimalisasi Penugasan Tidak Seimbang Menggunakan Metode Hungarian Pada Proses Pembuatan Glasswood - Muhammad Fiqri Fakhruddin; Wahyudin Wahyudin; Hamdani Hamdani (Peneliti.net, 2022)
The assignment problem is a problem that is often found in the handling of workers in a company. Accuracy in assignments is the main key to work more efficiently. However, it often happens when an inappropriate assignment makes performance unproductive. This can happen because there is idle time which results in the uneven distribution of an assignment, which increases production time. With this research is expected to help the problems in this company to be more optimal. Researchers used the Hungarian method to allocate assignments in order to obtain optimal results. Data obtained from observations to be tested in accordance with the method used. After the results were obtained manually, the results were then compared using the POM-QM software. The results of the assignment from the research are Ali installing the holder in 11 seconds, Kamal packing in 12 seconds, Iqbal doing the smoothing in 19 seconds, Yogi casting in 24 seconds, Taufik attaching the frame in 19 seconds, Budi giving glue with a time of 21 seconds, Gendon pasting photos with a time of 9 seconds, so the total processing time to produce Glasswood is 115 seconds/pcs